A new species of Pseudobunocephalus Friel, 2008 (Siluriformes: Aspredinidae) from the lower Tocantins and Mearim river drainages, North and Northeast of Brazil - Leão, Manuela Dopazo V.; Carvalho, Tiago P.; Reis, Roberto E.; Wosiacki, Wolmar B. (Zootaxa, 2019)
Pseudobunocephalus timbira, new species, is described from streams of the lower Tocantins and the Mearim river drainages, in North and Northeast of Brazil. Pseudobunocephalus timbira can be distinguished from all congeners by having the second hypobranchial and the third basibranchial cartilaginous (vs. ossified). Additionally, it can be dintinguished from P. lundbergi by the following putative apomorphic features within Pseudobunocephalus: posterolateral process of premaxilla present (vs. absent); bony knobs in dorsal lamina of Weberian apparatus absent (vs. present); distal end of posterior margin of 5th parapophysis not enlarged (vs. enlarged); number of ribs three (vs. four or five) and infraorbital sensory canal entering neurocranium via frontal (vs. via sphenotic). It is distinguished from P. bifidus and P. iheringii by having a gracile body not surpassing 34 mm SL (vs. robust body, reaching up to 59 mm SL, respectively); by having the posterior margin of cranial fontanel concave (vs. posterior margin somewhat straight with parieto-supraoccipital extending anteriorly); by having a conspicuous knobby ornamentation on dorsal surface of skull (vs. skull knobs slightly pronounced); by having Weberian ventral blade of hemal canal opened (vs. closed) and by the absence of serrations on the proximal portion of the anterior margin of pectoral-fin spine (vs. serrations covering entire anterior margin of the pectoral spine). Additionally, it can be distinguished from P. amazonicus, P. rugosus and P. quadriradiatus, by having the posterolateral mental barbel with at least one fleshy lobe located proximally along the posterior margin (vs. posterolateral mental barbel simple, not having fleshy lobes). It also differs from P. amazonicus and P. rugosus by having five branchiostegal rays (vs. four). It also can be distinguished from P. amazonicus by having the contact of hyomandibula cartilage with neurocranium limited to the sphenotic (vs. extending to both sphenotic and pterotic); by having the ventral blade of Weberian apparatus open (vs. closed) and by anterior exit of hemal canal in abdominal vertebra (vs. in complex vertebra); from P. rugosus by coloration of proximal portion of caudal fin similar to rest of caudal fin (vs. clear patch) and from P. quadriradiatus by the total number of pectoral fin-rays six (vs. five). Variable characteristics within Pseudobunocephalus species are summarized and comments on the phylogenetic relationships and the disjunct distribution of the new species are made. [Species zoobank url: urn:lsid:zoobank.org:act:392F95E0-86E1-4386-8779-C4F71098DBCC]